Antiskyrmions stabilized at interfaces by anisotropic Dzyaloshinskii-Moriya interactions - Markus Hoffmann; Bernd Zimmermann; Gideon P. Müller; Daniel Schürhoff; Nikolai S. Kiselev; Christof Melcher; Stefan Blügel (Nature Communications, 2017)
Skyrmions, localized defects in the magnetization, can be stabilised in materials by the Dzyaloshinskii-Moriya interaction (DMI). Hoffmann et al. predict that, when the DMI is anisotropic, antiskyrmions can be formed and coexist with skyrmions, enabling studies and exploitation of their interactions.